AN ANNOTATED TRANSLATION OF DAUGHTER - Ardhinie, Eka (Universitas Gunadarma, 2017)
The research aims are (1) To attain factual information concerning the porblems encountered of researcher during the process of translation of the source language into target language (2) To present plausible solutions to the problems encountered by the researcher during the porcess of translation. Keywords: Annotated, research, data, principle of translation, strategies of translation.